Christmas sweets ebook - Fluke, Joanne (2019)
Gathered in one delightful volume time, here are three yuletide tales of mystery, murder, and romance, featuring your favorite sleuths . . . THE TWELVE DESSERTS OF CHRISTMAS by JOANNE FLUKE It's the perfect mix of naughty and nice when two lovestruck boarding school teachers watch six kids over Christmas break. But when someone wants the cozy couple's romance to burn out faster than a scorched fruitcake, it's Hannah Swensen to the rescue . . . NIGHTMARE ON ELF STREET by LAURA LEVINE Aside from the mortifying costume, how bad can a gig as a mall Santa's elf be? Jaine Austen finds out when she's teamed up with the Santa from Hell. But things go from bad to worse when he's found murdered—and Jaine is suspected of being the naughty one . . . THE CHRISTMAS THIEF by LESLIE MEIER Elizabeth Stone is ready for a white Christmas in Tinker's Cove, Maine—until a fancy Yule ball at the Florida hotel where she works dumps snow on her plans. The sponsor's jewels have gone missing and the police are asking about her ties to a cute mystery guest. Good thing Elizabeth's mother, Lucy Stone, flew down to surprise her . . . Includes Luscious Holiday Recipes!